1996
DOI: 10.1021/jp9604094
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Investigation of Vibrational Effects on Magnetic Hyperfine Coupling Constants in the X3Σg- State of B2H2

Abstract: The influence of the vibrational motion on the magnetic hyperfine coupling constants (hfcc's) in the X 3 Σ gof B 2 H 2 is investigated by means of ab initio methods. The present study clearly shows that for the isotropic hfcc's of the boron centers the incorporation of the vibrational effects is essential already for the vibrational ground state. For the boron center the isotropic hfcc's calculated for the lowest vibrational state (A iso ( 11 B) ) -5.2 MHz) differ considerably from the value obtained at the eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Although the boron hydrides, particularly the binary boron species, have been the subject of numerous experimental and theoretical studies (see, for example, the reviews by Greenwood [42] and Downs and Pulham [43]), there is very little experimental information about the smallest member of the diborane hydrides family, Only recently Knight et al [44] reported the first definitive experimental characterization of this species by electron spin resonance in neon and argon matrices at 4 K. Controversial results of this study were explained by means of subsequent ab initio calculations [45]. Earlier experimental studies have achieved only fragmentary information concerning and its positive ion.…”
Section: Electronic Spectrum Ofmentioning
confidence: 84%
“…Although the boron hydrides, particularly the binary boron species, have been the subject of numerous experimental and theoretical studies (see, for example, the reviews by Greenwood [42] and Downs and Pulham [43]), there is very little experimental information about the smallest member of the diborane hydrides family, Only recently Knight et al [44] reported the first definitive experimental characterization of this species by electron spin resonance in neon and argon matrices at 4 K. Controversial results of this study were explained by means of subsequent ab initio calculations [45]. Earlier experimental studies have achieved only fragmentary information concerning and its positive ion.…”
Section: Electronic Spectrum Ofmentioning
confidence: 84%
“…The molecule has only been observed in rare gas matrices, where EPR (electron paramagnetic resonance) spectra indicated a triplet ground state 15 and an IR-spectrum revealed the ν 3 antisymmetric stretch at 2679.9 cm -1 . 16 [19][20][21][22] also focusing on the EPR properties 23 and most recently on the competition between multicenter and classical bonding. 24 However, no computations of the Renner-Tellersplit cation have yet been reported.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…Diborene 1 is a linear molecule of D ∞h symmetry with a 3 Σ g − ground state. 23 The highest singly occupied molecular orbitals (SOMO) are the [1π u (p x )] 1 [1π u p y ] 1 binding orbitals, so the formal bond order is 2. However, because the unpaired electrons are situated in orthogonal MOs, the double bond used in a Lewis-description is questionable in MO theory and therefore omitted from Scheme 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…study on B 2 H / 2 , including the correlation effects beyond The B 2 H 2 molecule is of great chemical interest because fourth-order perturbation theory. of the X 2 P u state of B 2 H / 2 (13,14) and to compute the with Those of Molecules of Lower Symmetry hyperfine coupling constants in the X 3 S 0 g state of the neutral (15). The electron-deficient nature stable structure had acetylene-like geometry.…”
Section: Introductionmentioning
confidence: 99%